The concept of Modesty in the Poetry of Behçet Necatigil - Al-Lami, Sawsan Azeez Khlaif (Al-Adab Journal, 2022)
Behçet Necatigil is considered one of the important Turkish authors in the 20th century. He was born in FATİH district in Istanbul in 1916 and died on 13 of December 1979 in Istanbul. The poet Necati started writing while he was very young. He had several important works in his short life that lasted only 63 years. Although he was creative in several and different works in literary types such as Drama, Translation, the art of conversing, and radio drama, the poet Behçet Necatigil who was known by his poetic identity, is considered one of the most important poets in Turkish literature and the successful one among them. The concept of modesty is a synonym to simplicity which includes several meanings such as not to be snobbish, or dictator which is a humane phenomenon in its concept. This concept of modesty is considered one of the positive conducts and one of the most important concepts that society respects and adopts it and eager to have it. In general, everyone aims at being a simple, moderate and not a snobbish person. Regardless of the spiritual and materialistic status of any person, this means that he adopted a lifestyle that is ordinary and simple. The poet Behçet Necatigil is one of the poets who adopted this situation all over their lives and was eager to be a moderate person. Thus, we see this concept clear in his poems. This is the reason that pushes us to write a research paper specifically on the poet Behçet Necatigil. We see that he is a person full of modesty and simplicity. He has largely and successfully used in his poems the concept of modesty as well as its derivatives. Our research paper will focus on this concept, and we will introduce a short summary about the life of the poet and his literary personality as well as his works. Then we sill study the concept of modesty in details. After that, we will expand our research paper to talk about how this concept has been used in the poems written by Behçet Necatigil.